Synergistic use of bioactive agents for the management of different skin conditions: an overview of biological activities - Baldi, M; Reynaud, R; Lefevre, F; Fleury, M; Scandolera, A; Maramaldi, G (European review for medical and pharmacological sciences, 2023)
Recently, many plant-derived bioactive agents have been included in dermo-cosmetics formulations. This leads to an extensive portfolio of innovative products with an expanded range of benefits, including anti-aging, antioxidant, hydrating and depigmenting. Although different technologies drawing on science and nature are used to create these high-performing molecules, there remains some debate about the mechanism of action of the natural bioactive ingredients within dermo-cosmetics. This review recapitulates the main biological mechanisms underlying the activity of natural active ingredients, with a specific focus on their synergistic use for the management of common, yet quite specific, skin conditions. A total of 28 plant-derived bioactives were selected from the Givaudan Active Beauty (Argenteuil, France) portfolio, a multinational company specializing in innovative natural actives research. An extensive literature review about their biological activity was conducted by a PubMed search using different keywords. No language or publication date restrictions were used. Givaudan Active Beauty data on file were also considered. The bioactive ingredients were described according to the pathogenetic mechanisms underlying 10 common skin conditions that dermo-cosmetics may address. Literature data have shown that plant-derived bioactives are involved in a wide range of biological mechanisms showing anti-inflammatory, antioxidant, and moisturizing properties, along with skin barrier protection and collagen synthesis activities. As a result, different combinations of bioactives within dermo-cosmetics can be defined to counteract simultaneously the different pathogenetic mechanisms underlying different skin conditions. Available literature supports the synergistic use of plant-derived bioactive agents within dermo-cosmetics as a viable and safe option for managing the most common skin conditions.